Multiple Facets of Nitrogen: From Atmospheric Gas to Indispensable Agricultural Input - Kabange, N. R.; Lee, So-Myeong; Shin, Dongjin; Lee, Ji-Yoon; Kwon, Youngho; Kang, Ju-Won; Cha, Jin-Kyung; Park, Hyeonjin; Alibu, Simon; Lee, Jong-Hee (Life, 2022)
Nitrogen (N) is a gas and the fifth most abundant element naturally found in the atmosphere. N’s role in agriculture and plant metabolism has been widely investigated for decades, and extensive information regarding this subject is available. However, the advent of sequencing technology and the advances in plant biotechnology, coupled with the growing interest in functional genomics-related studies and the various environmental challenges, have paved novel paths to rediscovering the fundamentals of N and its dynamics in physiological and biological processes, as well as biochemical reactions under both normal and stress conditions. This work provides a comprehensive review on multiple facets of N and N-containing compounds in plants disseminated in the literature to better appreciate N in its multiple dimensions. Here, some of the ancient but fundamental aspects of N are revived and the advances in our understanding of N in the metabolism of plants is portrayed. It is established that N is indispensable for achieving high plant productivity and fitness. However, the use of N-rich fertilizers in relatively higher amounts negatively affects the environment. Therefore, a paradigm shift is important to shape to the future use of N-rich fertilizers in crop production and their contribution to the current global greenhouse gases (GHGs) budget would help tackle current global environmental challenges toward a sustainable agriculture.
Keywords: nitrogen; agriculture; environment; sustainable food production